SO2 flux of COTOPAXI volcano, from the NOVAC data-base - Hidalgo, S.; Arellano, Santiago; Vasconez, F.; Arrais, S.; Bourquin, J.; Cordova, J.; Galle, Bo (Chalmers University of Technology, 2020)
This data-set presents volcanic gas emission data from NOVAC,
the global Network for Observation of Volcanic and Atmospheric Change.
For each volcano, data from one or several NOVAC Scanning mini-DOAS
instruments are combined with meteorological information to derive
daily statistics of total SO2 emission from the volcano.
Different versions of the data exist, depending on the algorithms
and meteorological information used in the evaluations.
Data is kindly made publicly available by the volcanological observatories
and institutions responsible for data collection and evaluation, on the
condition that credit is given according to the NOVAC Data Use Agreement.
Keywords: Climatology / Meteorology / Atmosphere; SO2 flux; Volcanic SO2 degassing; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Psychiatry; Psykiatri; Climate Science; Klimatvetenskap